Cement-based telegraph pole and preparation method thereof

By introducing composite freeze-thaw inhibitors into cement-based telephone poles, the multi-component synergy of graft modified polymers, lithium salts and nanoparticles are used to optimize the microstructure of cement-based materials, solving the problem of freeze-thaw resistance of cement-based telephone poles in extremely cold areas, and significantly improving the material's freeze-thaw resistance and durability.

CN119735410AInactive Publication Date: 2025-04-01XINGAN LEAGUE KUNXIANG POWER ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411933749.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The structural performance of cement-based telephone poles in the freeze-thaw cycle in extremely cold areas has deteriorated, resulting in material failure. The existing technology anti-freeze-thawing methods have limitations, making it difficult to effectively control stress concentration in low temperature environments.

Method used

Complex freeze-thaw inhibitors, including graft-modified polymers, lithium salts and nanoparticles, introduce hydrophilic and polar functional groups through chemical grafting, lithium salts reduce freezing point, and nanoparticles fill pores, and synergistically optimize the microstructure of cement-based materials.

Benefits of technology

It significantly improves the anti-freeze-thaw properties of cement-based materials, reduces the damage to the material structure by the freeze-thaw cycle, extends the service life of the material, and maintains good mechanical properties and stability in extreme environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a cement-based telegraph pole and a preparation method thereof.The cement-based telegraph pole is prepared from a cement-based building material, and the cement-based building material is characterized in that a composite freeze-thaw inhibitor is added into the cement-based material; the composite freeze-thaw inhibitor is composed of a polymer subjected to chemical grafting modification, a lithium salt and nanoparticles. Specifically, hydrophilic and polar functional groups are introduced into the graft modified polymer in a chemical grafting manner, the lithium salt has the effect of reducing the freezing point of the material, and the nanoparticles are used for filling pores in the material. The cement-based building material and the cement-based telegraph pole provided by the invention are suitable for cold and high-humidity regions, and can maintain good mechanical properties and stability in extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a cement-based utility pole and a preparation method thereof. Background Art

[0002] Cement-based materials play a vital role in modern construction projects. They are widely used in various building structures, power facilities and infrastructure projects. In particular, cement-based utility poles are key components of power transmission and distribution systems. Their stability and reliability are essential for the normal operation of the entire power network. However, in cold regions with extremely harsh climatic conditions, cement-based materials face severe challenges. These materials are often severely affected by freeze-thaw cycles, a natural phenomenon that causes the structural performance of the materials to gradually deteriorate and may even fail.

[0003] The main mechanism of freeze-thaw damage is that the water in the capillary pores inside the cement-based material freezes under low temperature conditions, and the huge pressure generated by the volume expansion of ice. This repeated pressure change caused by the formation and melting of ice will gradually lead to the expansion of microcracks inside the material, thereby affecting the overall structural integrity of the material. In addition to the impact of freeze-thaw cycles, complex environmental factors in cold regions, such as strong winds, snowfall and ice, will also cause additional loads on cement-based materials. These environmental factors not only increase the requirements for material crack resistance, but also pose higher challenges to the material's wind resistance and durability.

[0004] In dealing with the freeze-thaw resistance of cement-based materials, traditional technical means mainly rely on adding air-entraining agents or increasing the density of materials. However, these methods have certain limitations in practical applications. For example, although adding air-entraining agents can alleviate freeze-thaw damage to a certain extent, it may be at the expense of the mechanical properties of the material. Although increasing the density of the material helps to enhance its freeze-thaw resistance, the stress concentration problem inside the material is still difficult to be effectively controlled and solved in a low temperature environment.

[0005] As the application scenarios of cement-based utility poles become increasingly complex, there is an urgent need to develop an economical, efficient and comprehensive composite freeze-thaw inhibitor to meet the needs of various climatic conditions. Summary of the invention

[0006] In view of this, the present invention proposes a cement-based utility pole and a preparation method thereof, aiming to fill the deficiencies of the prior art and provide a new solution for improving the performance of cement-based materials.

[0007] The present invention provides a method for preparing a cement-based building material, comprising: Introducing a composite freeze-thaw inhibitor into a cement-based material, the composite freeze-thaw inhibitor is composed of a grafted modified polymer, a lithium salt and nanoparticles; wherein the grafted modified polymer introduces hydrophilic and polar functional groups through chemical grafting, the lithium salt lowers the freezing point, and the nanoparticles fill pores; The cement-based material introduced with the composite freeze-thaw inhibitor is sequentially mixed, stirred, poured and cured to prepare the cement-based building material.

[0008] Preferably, the graft-modified polymer is polyvinyl alcohol, polyacrylic acid or polyether polymer with carboxyl, hydroxyl or amino groups grafted onto the main chain of the molecule.

[0009] Preferably, the composite freeze-thaw inhibitor comprises the following components in weight ratio: Graft modified polymer: 5%-20%; Lithium salt: 2%-10%; Nanoparticles: 1%-8%; The rest was deionized water.

[0010] Preferably, the lithium salt is lithium nitrate and / or lithium fluoride; The lithium salt addition ratio is 2%-5% of the total weight of the cement-based material.

[0011] More preferably, the lithium salt is lithium nitrate.

[0012] Preferably, the nanoparticles are nano-silicon dioxide and / or nano-aluminum oxide.

[0013] More preferably, the nanoparticles are nano-silicon dioxide with a size of 10-50 nanometers.

[0014] More preferably, the nanoparticles are distributed in the cement matrix by mechanical dispersion and ultrasonic treatment.

[0015] Preferably, the cement-based material comprises a cement matrix raw material, a reinforcing filler, a hydrophobic agent and a modified aggregate.

[0016] Preferably, the cement matrix raw materials include ordinary Portland cement, high alumina cement, silica fume and graphene nanosheets; the reinforcing filler includes mineral fiber and nano-alumina particles; and the modified aggregate is a lightweight ceramsite aggregate with nano-titanium dioxide coated on the surface.

[0017] The present invention also provides a cement-based building material, which is prepared according to the above-mentioned method for preparing the cement-based building material.

[0018] The invention also proposes an application of the cement-based building material.

[0019] The present invention also provides a cement utility pole, which is prepared by using the above-mentioned cement-based building material.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Significantly improve the anti-freeze and thaw performance The present invention uses the synergistic effect of multiple components of the grafted modified composite freeze-thaw inhibitor to effectively reduce the generation and expansion pressure of ice crystals in the pores of cement-based materials under low temperature conditions, reduce the damage to the material structure caused by freeze-thaw cycles, and thus significantly improve the material's anti-freeze-thaw performance.

[0021] Tests show that compared with the traditional air-entraining agent method, the cement-based material prepared by the present invention has a mass loss reduced by more than 40% and a strength retention rate increased by more than 30% in a rapid freeze-thaw cycle test.

[0022] 2. Optimize material microstructure The present invention utilizes the synergistic effect of nanoparticles filling pores, grafting modified polymers to form a flexible protective layer, and lithium salts lowering the freezing point, thereby optimizing the pore structure of cement-based materials, reducing porosity, increasing closed porosity, and preventing water migration and pore connectivity.

[0023] Microscopic analysis (such as SEM and BET tests) shows that the material prepared by this method has a uniform pore size distribution and no obvious macroporous structure, which is significantly better than the effect of traditional air entraining agents or single lithium salt addition methods.

[0024] 3. Enhance durability and overall toughness The flexible network structure of the grafted modified polymer improves the crack resistance of cement-based materials and can effectively buffer the stress concentration caused by freeze-thaw cycles, thereby extending the service life of the material.

[0025] Long-term freeze-thaw tests show that the strength retention rate and durability of the cement-based material prepared by the present invention are significantly better than those of the comparative sample.

[0026] 4. Simple preparation process and controllable cost The present invention adopts a grafting modification, lithium salt and nanoparticle compounding strategy, has simple process steps and can be industrially produced, avoiding the complex bubble control and other special equipment requirements in traditional methods.

[0027] The amount of composite freeze-thaw inhibitor used in the material is small, the ratio is reasonable, and the overall cost is more advantageous than the use of high-performance air-entraining agents or other expensive admixtures.

[0028] 5. Strong environmental adaptability The invention is suitable for cold and high-humidity areas, can maintain good mechanical properties and stability under extreme environments, and broadens the application scope of cement-based materials.

[0029] Compared with the traditional air-entraining agent method, the material prepared by the present invention has more stable performance under extreme conditions and has no negative impact on the density of the material.

[0030] In summary, the present invention is significantly superior to the existing technology in terms of freeze-thaw resistance, material microstructure optimization, overall durability and economy, and has broad prospects for promotion and application. DETAILED DESCRIPTION

[0031] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0032] The present invention provides a cement-based material and a preparation method thereof, which specifically comprises: 1. Raw materials 1. Cement matrix raw materials Ordinary Portland cement: 50 parts by weight; High alumina cement: 20 parts by weight; Silica fume (microsilica powder): 5 parts by weight; Graphene nanosheets (to improve crack resistance and thermal conductivity): 0.5 parts by weight.

[0033] 2. Reinforced filler Mineral fiber (basalt fiber): 10 parts by weight; Nano-alumina particles: 5 parts by weight.

[0034] 3. Functional additives Hydrophobic agent (silane / siloxane emulsion): 2 parts by weight; Composite freeze-thaw inhibitor: 2 parts by weight.

[0035] Among them, the raw material composition of the composite freeze-thaw inhibitor includes: (1) Matrix material Polycarboxylate (PCE, molecular weight 2000-4000).

[0036] (2) Functional components Lithium salt (lithium nitrate LiNO3): freezing point inhibitor; Silane coupling agent (3-aminopropyltriethoxysilane, KH-550): improves interfacial bonding strength; Polyether polyol (molecular weight 1000-2000): enhances flexibility.

[0037] (3) Grafting monomer Acrylic acid (AA): provides carboxyl groups; Methacrylamide (MAM): Improves durability.

[0038] (4) Initiators and catalysts Potassium persulfate (KPS); Sodium sulfite (Na2SO3).

[0039] The preparation process of the composite freeze-thaw inhibitor includes: Step 1: Preparation of matrix solution Polycarboxylate (PCE) was dissolved in deionized water and stirred to form a 20 wt % solution.

[0040] Silane coupling agent (KH-550) was added and stirred at 50 °C for 30 min to promote the initial complexation between it and PCE.

[0041] Step 2: Graft polymerization Acrylic acid (AA) and methacrylamide (MAM) were mixed in a molar ratio of 1:1 and then slowly added dropwise to the above solution.

[0042] At the same time, add initiator (potassium persulfate, KPS) and catalyst (sodium sulfite, Na2SO3), control the temperature at 60-70°C, and react for 3 hours.

[0043] After the graft polymerization is completed, the mixture is cooled to room temperature to form a graft-modified polycarboxylate composite solution.

[0044] Step 3: Lithium salt compounding Add lithium nitrate (LiNO3) to the grafting solution and stir until completely dissolved. The lithium salt concentration is controlled at 2-3wt%.

[0045] Add polyether polyol to enhance the flexibility and tensile strength of the cement matrix through intermolecular interaction, and continue stirring for 1 hour.

[0046] Step 4: Drying and shaping The final composite solution is treated by a spray drying device to prepare a micro-powder composite freeze-thaw inhibitor.

[0047] The powder particle size is controlled at 1-5 μm so as to be evenly mixed with cement-based materials.

[0048] 4. Modified aggregate Modified lightweight ceramsite aggregate (surface coated with nano-titanium dioxide): 5 parts by weight; Water: water-cement ratio is 0.35-0.38.

[0049] 2. Preparation method Step 1: Raw material pretreatment Silica fume and graphene nanosheets are dispersed into water by ultrasonic dispersion technology to ensure uniform dispersion to form nano-enhanced slurry.

[0050] The basalt fiber was surface modified and coated with a silane coupling agent to improve its interfacial bonding strength with the cement matrix.

[0051] Step 2: Dry powder mixing Mix silicate cement, high alumina cement, nano alumina particles and composite freeze-thaw inhibitor in proportion, and use a high-efficiency mixer to stir for 10 minutes to ensure uniformity.

[0052] Step 3: Wet Mixing Gradually add the above dry powder mixture to the prepared nano-enhanced slurry while stirring (800-1000rpm). Add lightweight ceramsite aggregate and continue stirring for 5 minutes, and finally add the hydrophobic agent and mix well.

[0053] Step 4: Molding and Vibration The mixed slurry is poured into the mold and high-frequency vibration technology (20-30Hz) is used to eliminate bubbles and improve density.

[0054] Step 5: Maintenance Initial curing: Maintain 20℃ and humidity above 95% in the mold for 24 hours.

[0055] Post-low temperature curing: Place in a low temperature curing box (-10℃) for 5 days to simulate severe cold environment conditions.

[0056] Steam curing: Steam curing for 2 hours (70°C).

[0057] 3. Principle and Mechanism This method optimizes the internal microstructure and interface properties of cement-based materials through the synergistic effect of multiple components of grafted modified composite freeze-thaw inhibitors, thereby improving freeze-thaw resistance and durability. Its main principles and mechanisms include the following aspects: 1. Enhance dispersibility and interfacial bonding through grafting modification The introduction of polar and hydrophilic functional groups (such as carboxyl, hydroxyl, etc.) into the polymer molecular chain, the grafting modification process gives the composite freeze-thaw inhibitor better dispersibility and compatibility with the cement matrix. This modification brings the following effects: Uniform distribution: The uniform distribution of the inhibitor in the cement matrix effectively reduces stress concentration and the formation of local weak points.

[0058] Interface enhancement: The grafted functional groups are bonded to the hydration products of the cement matrix (such as calcium silicate hydrate CSH) through hydrogen bonds or ionic bonds, which enhances the interfacial bonding between the inhibitor and the matrix, thereby reducing the initiation and propagation of cracks.

[0059] 2. Multi-component synergistic effect reduces ice crystal formation and expansion stress Lithium salt component: Lithium salts (such as lithium nitrate) reduce the freezing point of water, inhibit the freezing of water in the pores, and reduce the volume expansion and internal stress caused by the formation of ice crystals.

[0060] Flexible polymer component: The polymer component forms a flexible film on the pore surface, which can absorb part of the expansion stress and provide additional barrier effect to mitigate the impact of freeze-thaw damage on the pore structure.

[0061] Nanoparticle filling: Nanoparticles (e.g., nanosilica) fill the micropores of the cement matrix, reducing the connectivity of the pores, thereby reducing the possibility of water migration and further weakening the impact of ice crystal formation on the structure.

[0062] 3. Optimize pore structure and reduce porosity and connectivity Through the combined effects of grafting modification and multi-component composite inhibitors, this method can significantly optimize the pore structure of cement-based materials: Reducing the proportion of large pores: Large pores are more likely to cause water accumulation and ice crystal expansion. This method converts large pores into small pores or closed pores through the filling effect of nanoparticles and polymers.

[0063] Improve the closed porosity: The formation of closed pores effectively blocks the water migration channel and reduces the path of freeze-thaw damage.

[0064] SEM and nitrogen adsorption tests show that the pore size distribution of the embodiment is more uniform, the porosity is significantly reduced, and the freeze-thaw resistance is further improved.

[0065] 4. Form a flexible network structure to enhance crack resistance The chemical and physical crosslinking between the grafted polymer and cement hydration products forms a flexible network structure: Buffering stress: The network structure can disperse the local stress generated by freeze-thaw cycles and delay the initiation and expansion of cracks.

[0066] Enhanced toughness: The flexible nature of polymers enhances the overall toughness of the material, making it more crack-resistant and durable in low-temperature environments.

[0067] 5. Improve the stability of hydration products The lithium salt component can interact with hydration products (such as CSH and ettringite) to form a denser and more stable hydration product structure: Reduce dissolution and migration: During freeze-thaw cycles, the dissolution and migration of hydration products are inhibited, maintaining the integrity of the matrix structure.

[0068] Stabilizing microstructure: The presence of lithium salt reduces the tendency of micro cracks to expand, significantly improving the long-term durability of the material.

[0069] 6. Conclusion From the perspective of microscopic mechanism, this method comprehensively improves the freeze-thaw resistance of cement-based materials from the molecular level to the microstructure through grafting modification and multi-component synergy: Graft modification optimizes the dispersibility and interfacial binding properties of the inhibitor.

[0070] Multiple components synergistically inhibit ice crystal formation and reduce expansion stress.

[0071] The optimized pore structure reduces the possibility of water migration and significantly slows down freeze-thaw damage.

[0072] The flexible network structure enhances the crack resistance and improves the overall durability of the material.

[0073] The stable hydration product structure provides more lasting anti-freeze-thaw performance support.

[0074] These microscopic mechanisms work together to give this method significant advantages in the application of cement-based materials in cold regions.

[0075] The present invention is described in detail below by using specific embodiments with different parameters set. The steps of the following embodiments are the same as the steps of the above method. Example 1

[0076] 1. Matrix solution Polycarboxylate (PCE): 20wt%; Silane coupling agent (KH-550): 1.5wt% (relative to the mass of PCE solution).

[0077] 2. Grafting monomer ratio Acrylic acid (AA): 2wt% (relative to the mass of PCE solution); Methacrylamide (MAM): 2wt%.

[0078] 3. Lithium salt addition amount Lithium nitrate (LiNO3): 3wt% (relative to the final solution mass); Polyether polyol: 1wt% (relative to the final solution mass).

[0079] 4. Reaction temperature and time Graft polymerization: 70°C, 3 hours; Powder particle size: 1-3μm. Example 2

[0080] 1. Matrix solution Polycarboxylate (PCE): 18wt%; Silane coupling agent (KH-550): 2wt%.

[0081] 2. Grafting monomer ratio Acrylic acid (AA): 1.5wt%; Methacrylamide (MAM): 2.5wt%.

[0082] 3. Lithium salt addition amount Lithium nitrate (LiNO3): 2wt%; Polyether polyol: 1.5wt%.

[0083] 4. Reaction temperature and time Graft polymerization: 65°C, 3.5 hours; Powder particle size: 2-5μm. Example 3

[0084] 1. Matrix solution Polycarboxylate (PCE): 15wt%; Silane coupling agent (KH-550): 1wt%.

[0085] 2. Grafting monomer ratio Acrylic acid (AA): 1wt%; Methacrylamide (MAM): 1.5wt%.

[0086] 3. Lithium salt addition amount Lithium nitrate (LiNO3): 1.5wt%; Polyether polyol: 0.8wt%.

[0087] 4. Reaction temperature and time Graft polymerization: 60°C, 2.5 hours; Powder particle size: 3-5μm.

[0088] Comparative Example 1 (without freeze-thaw inhibitor) No freeze-thaw inhibitors are added.

[0089] Comparative Example 2 (Traditional air entraining agent method) 0.02wt% of air entraining agent was added to ordinary cement mortar with the goal of alleviating freeze-thaw damage by improving the pore structure distribution.

[0090] Comparative Example 3 (Single Lithium Salt Addition Method) The composite freeze-thaw inhibitor was replaced with 3wt% lithium nitrate.

[0091] Test Example 1 The products obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the performance testing method included: 1. Freeze-thaw cycle test (GB / T50082-2009) The rapid freeze-thaw cycle method was adopted: the freeze-thaw temperature range was -20°C to 20°C, each cycle was 4 hours, and the relative dynamic elastic modulus and mass loss rate of the sample were tested after 100 freeze-thaw cycles.

[0092] 2. Compressive strength retention rate test (GB / T17671-2021) Test the compressive strength of the sample before and after the freeze-thaw cycle, and calculate the compressive strength retention rate: Retention rate = (compressive strength after freeze-thaw / initial compressive strength) × 100%.

[0093] 3. Microstructure analysis (SEM and porosity test) The micro crack distribution was observed by scanning electron microscopy (SEM), and the porosity change was determined by nitrogen adsorption method.

[0094] The experimental results are shown in Table 1.

[0095] Table 1 sample Freeze-thaw cycles Relative dynamic elastic modulus (%) Mass loss rate (%) Compressive strength retention rate (%) Porosity(%) Example 1 100 92.5 0.8 91.2 12.8 Example 2 100 88.3 1.2 87.5 13.5 Example 3 100 84.6 1.5 83.7 14.1 Comparative Example 1 100 63.5 5.8 59.4 18.6 Comparative Example 2 100 77.2 3.6 73.5 16.4 Comparative Example 3 100 81.5 2.7 79.2 15.8 As can be seen from Table 1, the relative dynamic elastic modulus, mass loss rate and compressive strength retention rate of the products of Examples 1-3 are better than those of Comparative Examples 1-3 after 100 freeze-thaw cycles. This shows that the freeze-thaw resistance of cement-based materials can be significantly improved by adding a composite freeze-thaw inhibitor of polycarboxylate, silane coupling agent, grafting monomer, lithium salt and polyether polyol. Specifically, the product of Example 1 performed best in all test indicators, with a relative dynamic elastic modulus of 92.5%, a mass loss rate of 0.8%, a compressive strength retention rate of 91.2%, and a porosity of 12.8%, showing excellent freeze-thaw resistance and low porosity.

[0096] Although Examples 2 and 3 are slightly inferior to Example 1 in various performance indicators, they still have obvious performance improvements compared to Comparative Examples 1 to 3. This shows that even under different matrix solution concentrations, grafting monomer ratios, lithium salt addition amounts and reaction conditions, cement-based materials with good freeze-thaw resistance can still be prepared through reasonable formulation design and process control.

[0097] Since no freeze-thaw inhibitor was added to Comparative Example 1, its performance index was significantly lower than that of the embodiment, indicating that the addition of freeze-thaw inhibitor is necessary to improve the freeze-thaw resistance of the material.

[0098] Comparative Example 2 adopts the traditional air entraining agent method. Although the pore structure distribution is improved to a certain extent, its performance index is still not as good as that of the embodiment, which shows that it is not enough to alleviate the freeze-thaw damage only by improving the pore structure distribution, and it needs to be combined with the synergistic effect of other chemical components.

[0099] Comparative Example 3 only added lithium nitrate. Although the freeze-thaw resistance was improved to a certain extent, the effect was not as good as that of the embodiment. This may be because the addition of a single lithium salt is not sufficient to provide adequate freeze-thaw protection and needs to be used in combination with other components such as polyether polyols to achieve better results.

[0100] In summary, through the formulations and processes of Examples 1-3, cement-based materials with excellent freeze-thaw resistance can be prepared, which provides an effective solution for practical engineering applications.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a cement-based building material, characterized in that: include: Introducing a composite freeze-thaw inhibitor into a cement-based material, the composite freeze-thaw inhibitor is composed of a grafted modified polymer, a lithium salt and nanoparticles; wherein the grafted modified polymer introduces hydrophilic and polar functional groups through chemical grafting, the lithium salt lowers the freezing point, and the nanoparticles fill pores; The cement-based material introduced with the composite freeze-thaw inhibitor is sequentially mixed, stirred, poured and cured to prepare the cement-based building material.

2. The method for preparing cement-based building materials according to claim 1, characterized in that: The graft-modified polymer is polyvinyl alcohol, polyacrylic acid or polyether polymer with carboxyl, hydroxyl or amino groups grafted onto the main chain of the molecule.

3. The method for preparing cement-based building materials according to claim 1, characterized in that: The composite freeze-thaw inhibitor comprises the following components in weight ratio: Graft modified polymer: 5%-20%; Lithium salt: 2%-10%; Nanoparticles: 1%-8%; The rest was deionized water.

4. The method for preparing cement-based building materials according to claim 1, characterized in that: The lithium salt is lithium nitrate and / or lithium fluoride; The lithium salt addition ratio is 2%-5% of the total weight of the cement-based material.

5. The method for preparing cement-based building materials according to claim 1, characterized in that: The nanoparticles are nano silicon dioxide and / or nano aluminum oxide.

6. The method for preparing cement-based building materials according to claim 1, characterized in that: The cement-based material comprises a cement matrix raw material, a reinforcing filler, a hydrophobic agent and a modified aggregate.

7. The method for preparing cement-based building materials according to claim 6, characterized in that: The cement matrix raw materials include ordinary silicate cement, high-alumina cement, silica fume and graphene nanosheets; the reinforcing filler includes mineral fiber and nano-alumina particles; and the modified aggregate is a lightweight ceramsite aggregate with nano-titanium dioxide coated on the surface.

8. A cement-based building material, characterized in that: The cement-based building material is prepared according to the method for preparing a cement-based building material according to any one of claims 1 to 7.

9. Use of the cement-based building material according to claim 8.

10. A cement utility pole, characterized in that: The cement utility pole is prepared by the cement-based building material according to claim 8.

Citation Information

Patent Citations

  • Liquid concrete anti-freezing agent

    CN102674747A

  • High-durability cement-based composite material and preparation method thereof

    CN113213853A

  • C50 second-generation recycled concrete suitable for severe cold areas and preparation method thereof

    CN117510144A

  • Sulphoaluminate cement-based negative temperature pressure slurry and preparation method thereof

    CN117735942A

  • Cement composition

    JP1999079817A